Value of extracorporeal artificial liver support in pediatric acute liver failure: A single-center experience of over 10 years - Ocak, Ilhan (Frontiers in Pediatrics, 2023)
Purpose Acute liver failure (ALF) is a life-threatening disease characterized by rapid-onset liver dysfunction, coagulopathy, and encephalopathy in patients without chronic liver disease. Today, the combined application of continuous veno-venous hemodiafiltration (CVVHDF) and plasma exchange (PEX), which are forms of supportive extracorporeal therapy (SECT), with conventional liver therapy in ALF is recommended. This study aims to retrospectively analyze the effects of combined SECT in pediatric patients with ALF. Materials and Methods We retrospectively analyzed 42 pediatric patients followed in the liver transplantation intensive care unit. The patients had ALF and received PEX supportive therapy with combined CVVHDF. The biochemical lab values of the patients before the first combined SECT and after the last combined SECT were analyzed comparatively. Results Of the pediatric patients included in our study, 20 were female and 22 were male. Liver transplantation was performed in 22 patients, and 20 patients recovered without transplantation. After the discontinuation of combined SECT, all patients had significantly lower serum liver function tests (Total bilirubin, ALT, AST), ammonia, and PT/INR levels from the first levels (p<0.01). Hemodynamic parameters (i.e., mean arterial pressure [MAP]) also improved significantly. Discussion & Conclusion Combined CVVHDF and PEX treatment produced significant improvement in biochemical parameters and clinical findings, including encephalopathy, in pediatric patients with ALF. PEX therapy combined with CVVHDF is a proper supportive therapy for bridging or recovery.